Efek Pemaparan Ekstrak Etanol dan Ekstrak Air Sirih Merah (Piper crocatum) terhadap Hidrofobisitas Permukaan Sel Staphylococcus aureus - Farida Rachmawaty (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2010)
Red betel vine has been proved having the benefit as antibacterial toward Staphylococcus aureus1 While bacteria infected usually hydrophobic interaction before. The purpose of the research is to know the ethanol extr&ct and water extract effect toward Staphylococcus  ureus surface hydrophobicity and to know the different effect between ethanol extract and water extract. The research is laboratory experimental. Ethanol extract and water extract consentration was made with dilution method so the concentration extracts were 25%, 12.5%, 6.25%, 3.13%, 1.57%, 0.84% and 0.42%. The method was used for determine cell surface hydrophobicity is based on Koga et a/ modification. 2 Cell surface hidrophobicity of bacteria was compared between before and after exposure with ethanol and water extract. The measuring used spectrophotometer The result was analyzed using Mann-Whitney test with SPSS programme. Hydrophobicity of Staphylococcus aureus cell surface was decreased on the exposure of ethanol extract or water extract of red betel vine. The first extract addition sharply decreased the hydrophobicity and the decrease became lower. This result is appropriate with the research of Razak et a/. 3 The decreasing hydrophobicity of Staphylococcus aureus cell surface is not significantly different between ethanol extract and water extract of red betel vine (p>O. 05). Ethanol extract and water extract of red betel vme (Piper crocatum) have decreasing effect for Staphylococcus aureus A TCC 25923 cell surface. The exposure etahnol ectract and water extract of red betel vine is not significantly different.